PERBEDAAN EFEKTIVITAS EKSTRAK RIMPANG TEMULAWAK (Curcuma xanthorriza Roxb.) DENGAN EKSTRAK DAUN SALAM (Eugenia polyantha Wight) PADA PENURUNAN KADAR KOLESTEROL TOTAL TIKUS PUTIH JANTAN (Rattus norvegicus) - Rizki, Ayu Ulan; Cholid, Cholid; Amalia, Muttia (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Dyslipidemia is a coronary heart disease risk factor. Dyslipidemia is characterized by the elevated levels of LDL, triglycerides, total cholesterol, and the decrease in HDL. Ginger rhizome (Curcuma xanthorriza Roxb.) and bay leaf (Eugenia polyantha Wight.) are local plants that have the abilities to decrease total cholesterol. This research design was true experimental with pre- and post-control group design. Criteria of sample were white rats, wistar strain, male, age of 8-12 weeks, and body weight range of 150-200 grams. Sampling method was simple random sampling. The experimental rats were acclimatized for seven days. Hypercholesterol diet was fed two weeks, and then the rats were given intervention and get hypercholesterol diet for two weeks. During intervention, the experimental rats were divided into 6 groups of administrationi.e, rats administered with 1) carboxymethil celluse/CMC, 2) simvastatin 0,9 mg/kg BW/day, 3) ginger rhizome extract 200 mg /kg BW/day, 4) ginger rhizome extract 400 mg/kg BW/day, 5) bay leaf extract 200 mg/kg BW/day, and 6) bay leaf extract 400 mg/kg BW/day. Blood samples were taken from caudal vein and total cholesterol levels were measured by spectrophotometry. The analysis used paired T test, One Way ANOVA test. The results showed ginger rhizome extract did not effectively reduce total cholesterol. However, bay leaf extract effectively decreased total cholesterol levels with the highest total cholesterol reduction was found in rats administered with dose of 400 mg/kg BW/day i.e, 15.4 mg/dl. Bay leaf extract have the same effectivity with simvastatin as a standard drug in lowering cholesterol level.